Metabonomic analysis of the anti-hepatic fibrosis effect of Ganlong capsules - Lv, ChangLing; Li, YinRui; Ou, Ling; Zhou, Jie; Peng, Fang; Wu, DingYu (Frontiers in Pharmacology, 2023)
Context: Hepatic fibrosis is a progressive condition, often attributed to metabolic disorders, which may promote cirrhosis and liver cancer. Ganlong capsules derived from Periplaneta Americana have been shown to have a therapeutic effect on liver fibrosis but little is known about the molecular mechanisms involved. Objective: To investigate the metabolic modulations produced by Ganlong capsules in liver fibrosis. Methods: A carbon tetrachloride- (CCl4) treated rat model of liver fibrosis was constructed and Ganlong capsules administered. Levels of serum liver enzymes and pathological changes to the liver were evaluated. Non-targeted metabolomics of liver, serum and urine were used to investigate metabolic regulatory mechanisms. Results:Ganlong capsules reduced serum levels of liver enzymes and improved pathological changes in the rat model of fibrosis. Non-targeted metabolomics showed that Ganlong capsules ameliorated pathways of glycerophospholipid, linoleic acid, pyrimidine, glycine, butyric acid, valine, serine, threonine and arachidonic acid metabolism and biosynthesis of leucine and isoleucine. Such pathways influence the development of CCl4-induced liver fibrosis. Conclusion:Ganlong capsules had an anti-fibrotic hepatoprotective effect and regulated lipid, butyric acid, amino acid and arachidonic acid metabolism.